Occupational accidents: an integrative review - Andrea Prochnow; Tânia Solange Bosi de Souza Magnago; Juliana Petri Tavares; Carmem Lúcia Colomé Beck; Rosângela Marion da Silva; Marinez Diniz da Silva Ceron; Rafael Ravalia de Castro (Universidade Federal de Santa Maria, 2012)
Objective: the research aimed to identify and analyze the available online scientific productions in Brazilian literature on the subject of occupational accidents. Method: it is an integrative review, using the keyword "occupational accident". Papers published in English have been selected, fully available online, in databases like LILACS, BDENF and SCIELO between 2004 and 2010. The Data collection was performed between the months of July and August 2010. Results: it has been shown the predominance of cross-sectional studies conducted in hospitals and with nursing workers in the year 2009. The accidents that took place in the South and Southeast regions were the most studied. Most of these studies aimed to characterize occupational accidents. Conclusions: Investment both from institutions and workers are needed, in order to promote better health and fewer accidents in working environments